Family Psychoeducation dalam Meningkatkankan Kemampuan Keluarga Merawat Anggota Keluarga dengan Skizofrenia - Anggraini, Yunita; Keliat, Budi Anna; Putri, Yossie Susanti Eka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the implementation of family psychoeducation in caring for family members with schizophrenia. The method used in this study is to use a literature review approach. The databases used in the literature search were Pubmed, Science direct, Scopus, and Spinger link using the keywords family psychoeducation, family intervention, schizophrenia, caregiver burden, family burden. The results showed that family psychoeducation can increase family knowledge, reduce anxiety and reduce family burden in caring for patients with schizophrenia. The conclusion based on the analyzed articles is that family psychoeducation is effective in improving the family's ability to care for family members with schizophrenia. Keywords: Family Burden, Family Psychoeducation, Schizophrenia,